1968
DOI: 10.1021/jf60159a012
|View full text |Cite
|
Sign up to set email alerts
|

Esterases of mouse brain active in hydrolyzing organophosphate and carbamate insecticides

Abstract: A number of hydrolytic enzymes of mouse brain are detected by a thin-layer agar gel electrophoresis technique. Each of the 13 bands of esterase activity was tested against various substrates, including insecticidal, radiolabeled organophosphates and carbamates, to characterize the abilities of these esterases to degrade these insecticides and their analogs. Three cathodally moving and eight anodally moving bands show appreciable amounts of insecticide-degrading activity. The latter bands can be subdivided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
1

Year Published

1971
1971
1986
1986

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…It was surprising that the latter enzymes, at least, did not show any abilities to degrade organophosphates except for the weak degradation activities against parathion. This marks a great contrast to the results obtained for mouse brain A-type esterase (Sakai and Matsumura, 1968), where most of A-type esterases separated by similar electrophoretic means appeared to be correlated to organophosphate degradation activities.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It was surprising that the latter enzymes, at least, did not show any abilities to degrade organophosphates except for the weak degradation activities against parathion. This marks a great contrast to the results obtained for mouse brain A-type esterase (Sakai and Matsumura, 1968), where most of A-type esterases separated by similar electrophoretic means appeared to be correlated to organophosphate degradation activities.…”
Section: Discussioncontrasting
confidence: 99%
“…Inhibitors and labeled insecticides used in this study were Department of Entomology, University of Wisconsin, Madison, Wisconsin 53706. identical to the ones described by Sakai and Matsumura (1968) except for the ring-labeled Famphur [o,p-(dimethylsulfamoyl)phenyl , -dimethyl phosphorothioate] which was obtained from American Cyanamid Co.…”
Section: Methodsmentioning
confidence: 99%
“…Both carbaryl and dieldrin are known inhibitors of esterases and oxidative enzymes in the microsomal fraction of mammalian cells (Gillett and Chan, 1968; Sakai and. Matsumura, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…A study of Sakai and Matsumura (1968) has given evidence that the action of carbaryl is not limited to acetylcholinesterase, but may inhibit other esterases as well. In their investigation, it was found that a number of esterases isolated from mouse brain were capable of hydrolyzing both carbamate and organophosphorus compounds.…”
mentioning
confidence: 99%
“…Preliminary results indicate coincidence of both enzymes after Sephadex G-100 chromatography as well as DEAEcellulose chromatography, indicating that both reactions are probably mediated by the same enzyme. In the case of malathion resistance in various species, the nonspecific esterases appear to be identical to carboxylesterases because there is some evidence which suggested that carboxylesterases have nonspecific esterase activities (Main and Braid, 1962) or nonspecific esterases have carboxylesterase activities (Matsumura and Sakai, 1968;Miyata and Matsumura, 1971; Sakai and Matsumura, 1968). In the case of fenthion resistance in the mosquito, Culex pipiens fatigans (Stone and Brown, 1969), it is probable that a phosphatase was identical to the a-and ß-naphthyl acetate hydrolyzing enzyme.…”
Section: Possible Roles Of Nonspecific Esterasesmentioning
confidence: 99%